Toksisitas Akut dan Khasiat Ekstrak Som Jawa (Talinum paniculatum Gaertn) sebagai Stimulan - Yun Astuti Nugroho; Lucie Widowati; Pudjiastuti Pudjiastuti; Budi Nuratmi (JURNAL ILMU KEFARMASIAN INDONESIA, 2005)
Som Jawa (Talinum paniculatum Gaertn.) is a kind of Indonesian herbs that has similarities morphologically and chemically to Chinese ginseng. Som Jawa known as Ginseng Jawa in traditional healing has been made into various forms. The famous form is made as wine. The research on acute toxicity and efficacy test of Som Jawa as stimulant have been carried out to make Som Jawa into Indonesian Ginseng. The methodology of toxicity test is according to Weil CS (1952) and the efficacy test is according to Turner (1965). The test result showed that the value of acute toxicity of Som Jawa is 32.22 (25.59-40.56) mg/10 g BW (ip mice). At the time of starting to sleep, there was a significant difference on Som Jawa 10 mg/40g BW dose administration to Heptamyl 1.56 mg/40 g BW (p=0.00). In the swimming time extract of Som Jawa 5 and 10 mg/40 g BW showed no significant differences to Heptamyl 1.56 mg/40 g BW (p>0.05) (mean=32.88 +11.6;39.77 +14.6; 32.33 – 15.9). Som Jawa (Talinum paniculatum Gaertn.) is safe based on acute toxicity test. Extract of Som Jawa could prolong the time of starting to sleep and improve fitness.